Formation Consensus Control Method With Time-Varying Parameters Based on Virtual Leader - Hongyun Wang; Xiwei Guo; Wenzhao Li; YaQin Li; Weiwei Gao (International Journal of Aerospace Engineering, 2025)
A method of formation pattern alternation and consistent flight control in complex battlefield environment is put forward, considering the single formation pattern during formation flight and failing to deal with the changeable battlefield environment. The virtual leader’s consistent reference state model is constructed, and the control law model under constant reference state and time-varying reference state is designed. The necessary and sufficient conditions for followers to track virtual leader consistently are given in accordance with fixed topology and dynamic switching topology. To realize formation control, the time-varying trajectory consensus controller with virtual leader reference state is proposed. The visual operation interface is designed which can make the formation generation process easy to operate. The simulation results show that the method has realized the dynamic switching of formation pattern and the flexible setting of formation size in complex battlefield environment, and the consistent tracking of formation follower to virtual leader and the consistent flight of formation, which provides support for the development of key technology of cluster equipment.